Decision Making Factors In An Ecotourism Visit In The Situ Gunung Natural Tourism Park West Java - Sukamdani, Hariyadi B; Sulistyadi, Yohanes; Sukwika, Tatan; Sukamdani, Nugroho B; Eddyono, Fauziah (The Graduate School of Sahid University, 2024)
The Situ Gunung Nature Tourism Park (TWA) is a conservation area that was developed by prioritizing the concept of ecotourism. However, the ecotourism program created could have been more optimal, considering the requests and desires of visitors. This research aims to determine the factors that underlie decision-making for ecotourism visits at TWA Situ Gunung, West Java. The variables explained include the concept of ecotourism, intention to revisit, perception of cleanliness, and ticket price differentiation. The method used in this research is SmartPLS to test the proposed hypothesis. The analysis results show that ticket prices negatively influence ecotourism visits, with a coefficient of -0.058 (H1). On the other hand, cleanliness has a positive effect with a coefficient of 0.224 (H2), and security has a positive impact of 0.180 (H3). The accessibility factor is proven to have the most significant influence on ecotourism visits, with a coefficient of 0.464 (H4). The results of this research indicate that to increase ecotourism visits, managers need to focus on improving accessibility and cleanliness, as well as reconsidering ticket pricing strategies. Thus, this research contributes to the development of ecotourism that is more responsive to visitor needs and preferences, increasing visits and supporting conservation desires at Situ Gunung TWA.